2019
DOI: 10.1039/c9ra09355a
|View full text |Cite
|
Sign up to set email alerts
|

The promotion and suppression of DNA charge neutralization by the cosolute ectoine

Abstract: Ectoine, a cosolute and osmolyte, is used by extremophilic microorganisms to maintain an osmotic equilibrium of cells with their surrounding medium under conditions of extreme salinity or thermal and pressure stresses. It is also considered a protectant of biomolecules such as protein and DNA in cells. In the present study, we investigate its influence on DNA charge neutralization and compaction through dynamic light scattering (DLS), atomic force microscopy (AFM) and single molecular magnetic tweezers (MT). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The process is always companied by DNA charge neutralization by the counterion [ 36 ]. When DNA is mixed with positively charged polyelectrolytes such as cationic polymers, polymerization formation or macrophase separation often occurs [ 21 ]. Since DNA is negatively charged in solution, the process of DNA compaction must overcome the electrostatic repulsion between segments of DNA so that one or few DNA chains can form a more compact and ordered structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process is always companied by DNA charge neutralization by the counterion [ 36 ]. When DNA is mixed with positively charged polyelectrolytes such as cationic polymers, polymerization formation or macrophase separation often occurs [ 21 ]. Since DNA is negatively charged in solution, the process of DNA compaction must overcome the electrostatic repulsion between segments of DNA so that one or few DNA chains can form a more compact and ordered structure.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous mechanical measurement of DNA–lysozyme complexes in optical tweezers [ 1 ], they found that the persistence length of DNA–lysozyme complexes exhibits a nonmonotonic behavior as a function of the protein concentration. We have studied DNA complexes at various ionic and solution conditions in the past [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…14,24 The procedure can be described briey as follows: a DNA chain is bound at one end to an immobile support (the glass sidewalls) and at the other end to a paramagnetic bead. [18][19][20][21] A permanent magnet controlled by a micromanipulator system (MP-285), Sutter Instruments (Novato, CA, USA) is used to exert a force on the paramagnetic bead to pull tethered DNA. The movement of paramagnetic bead was recorded by a CCD camera in real-time.…”
Section: Tethering Dna By Magnetic Tweezers (Mt)mentioning
confidence: 99%